An Experimental Study of WSN Power Efficiency: MICAz Networks with XMesh - Tyler W. Davis; Xu Liang; Miguel Navarro; Diviyansh Bhatnagar; Yao Liang (International Journal of Distributed Sensor Networks)
This is an investigation of Wireless Sensor Networks (WSNs) using Memsic's XMesh routing protocol on MICAz wireless motes. It focuses on the study of the practical aspects of WSNs' power efficiency and network characteristics, which play a critical role in real-word WSN deployments for environmental monitoring. Based on an experimental study and following a quantitative approach, this work examines XMesh's high power and low power operation modes and the data transmission intervals, among other factors. Route utilization was identified as a major contributor of the mote's battery use. A field study was conducted as a point of comparison and the results obtained were comparable to the laboratory tests with regards to the battery life and the mote's route utilization. The network reliability was found to be considerably lower in the field study. In addition, it was found that the original WSN gateway, used during the study, presented severe practical limitations regarding the system's robustness and reliability. To address these problems, we present a solution based on our integrated network and data management system, which successfully facilitates the deployment of a new WSN gateway and significantly improves the operational robustness and reliability of the WSN system.